Warunki kredytów dla rolników w bankach spółdzielczych i komercyjnych w Polsce - Daniłowska, Alina; Kobus, Paweł (The Terms of Credits for Farmers in Cooperative and Commercial Banks in Poland, 2006)
In the paper the terms of agricultural credits granted by commercial banks are compared with the terms of such kind of credits offered by cooperative banks. The analysis shows that the differences in the terms of credits for working capital are much greater than the differences in the terms of investment credits. Commercial banks seem to be more flexible in setting the terms of credits for farmers.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 173-179